Time for a Drink? A Mathematical Model of Non-human Primate Alcohol Consumption - Moore, Sharon; Radunskaya, Ami; Zollinger, Elizabeth; Grant, Kathleen A.; Gonzales, Steven; Baker, Erich J. (Frontiers in Applied Mathematics and Statistics, 2019)
We simulate a non-human primate's alcohol drinking pattern in order to better understand temporal patterning of alcoholic drinks that can lead to the excessive intakes associated with alcohol use disorder. A stochastic mathematical model of alcohol consumption pattern is developed, where model parameters are calibrated to an individual's drinking history. The model predicts a time series that simulates a monkey's alcohol intake in time, and we analyze this drinking pattern to understand the variations in day and night drinking, the lengths of drinks (intake in 5 or more consecutive secs), and lengths of bouts (1 or more drinks per 5 min occasion). This time series can predict a lifetime categorical drinking levels (light, binge, heavy, or very heavy), thus correlating an individual's parameters with distinct long term drinking classifications.